Analisis Komposisi, Timbulan dan Potensi Daur Ulang Sampah Pada Kawasan Wisata Pantai Natsepa, Kabupaten Maluku Tengah - Juliana W. Tuahatu; Novianty Tuhumury; Gratia D. Manuputty (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2023)
Natsepa Beach is one of the famous tourist areas on Ambon Island. The presence of tourists in the area contributes to the production of both organic and inorganic waste which affects not only the aesthetics of the area but also the income of economic agents. The study aims to analyse waste composition, waste generation, and the recycling potency in Natsepa Beach. The study was conducted from July to August 2022 by applying a field observation method. The procedure of SNI 19-3964-1994, which regards urban waste collection methods to measure the composition and waste generation, was applied in this research. The results showed that the amount of organic waste, which is dominated by fruit peel waste (from rujak or fruit salads), is about 92.21%, whereas it is only about 7.79% of inorganic waste that comes from plastic waste. Total weight of waste that is generated by a person is around 0.12 kg/day or 0.46 liters/day in volume standard. Thus, it can be assumed that every visitor in Natsepa Beach produces 0.12 kg (0,11 kg of organic and 0,01 kg of inorganic waste). The potency to recycle organic waste into compost is 100% and eco enzyme is 78.52%. Furthermore, the potential plastic waste recycling is about 77.19%.